Arbitrary Palliation of Ruptured Abdominal Aortic Aneurysms in the Elderly is no Longer Warranted. Issue 6 (June 2016) - De Rango, P.; Simonte, G.; Manzone, A.; Cieri, E.; Parlani, G.; Farchioni, L.; Lenti, M.; Verzini, F.
Abstract : Objective/Background: A consistent number of elderly patients with ruptured abdominal aortic aneurysms (rAAAs) are deemed unfit for repair and excluded from any treatment. The objective of this study was to examine the impact on survival of endovascular repair and open surgery with restricted turndown in acute AAA repair. Methods: A prospective database for patients treated for rAAA was established. None of the patients admitted alive with rAAA were denied treatment. Multivariate regression models, the predictive risk assessment Glasgow Aneurysm Score (GAS), and subgroup analyses in older patients were applied to identify indicators of excessive 30 day mortality risk that could affect the decision for turndown. Results: From 2006 to 2015, 113 consecutive patients (93 males; mean age 77.2 years) with rAAAs were treated (69 open surgery; 44 EVAR). Overall peri-operative (30 day) mortality was 38.9% (44/113): 40.6% (28/69), and 36.4% (16/44) after open surgery and EVAR, respectively ( p  = .70). Multivariate logistic regression identified old age as an indicator of increased peri-operative mortality (odd ratio [OR] 1.2, 95% confidence interval [CI] 1.1–1.3; p  = .001), as well as free aneurysm rupture (OR 5.0, 95% CI 1.3–19.9; p  = .02). GAS was higher in patients who died (97.75 vs. 86.62), but the score failed to identify increased peri-operative mortality risk in adjusted analyses (OR 1.0; p  = .06). Almost two thirds of the patients ( n  = 71) were older than 75 at the time of aneurysm rupture (48.6% octogenarians) and EVAR was more commonly applied than open surgery (86.4% vs. 47.8%; p  < .0001). Peri-operative mortality in > 75 year old patients was 46.5% compared with 26.2% in younger patients ( p  = .05), with rates increased after open surgery (54.5% vs. 27.8%, p  = .03) but not after EVAR (39.5% vs. 16.7%; p  = .39). According to Kaplan–Meier estimates, mean survival was 39.7 ± 4.8 months. Patients older than 75 years of age survived for a mean of 23.0 ± 4.47 months after rupture. Conclusion: In this study aggressive treatment with a very restricted or no turndown strategy for any rAAA, also applied to older patients, allowed for an additional mean 40 months of survival after aneurysm rupture. In the contemporary endovascular era the decision to deny repair arbitrarily to older patients with rAAAs must be revisited.